2004
DOI: 10.1074/jbc.m402781200
|View full text |Cite
|
Sign up to set email alerts
|

Stearoyl-CoA Desaturase 1 Gene Expression Is Necessary for Fructose-mediated Induction of Lipogenic Gene Expression by Sterol Regulatory Element-binding Protein-1c-dependent and -independent Mechanisms

Abstract: Stearoyl-CoA desaturase (SCD) synthesizes oleate necessary for the biosynthesis of triglycerides and other lipids. Mice with a targeted disruption of the SCD1 gene are deficient in tissue oleate and have reduced expression of the sterol regulatory element-binding protein (SREBP) and its target genes. The SREBP-1c isoform is a known mediator of insulin action on hepatic gene expression, but its transcriptional effects due to glucose or fructose are still unclear. We found that fructose compared with glucose is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
215
6
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 261 publications
(238 citation statements)
references
References 65 publications
15
215
6
1
Order By: Relevance
“…In mice with on a pure 129 SV background, fructose supplementation induces fatty liver. 27 Fructose induces the hepatic expression of SCD1 and other lipogenic proteins in SREBP-1c-knockout mice, but not in SCD1-knockout mice, 27 indicating that SCD1 expression is important for the development of fructose-induced fatty liver. However, in ddY mice, sucrose supplementation increased SREBP-1c mRNA and that of its target genes FAS and ACC1 but did not affect SCD1 mRNA expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In mice with on a pure 129 SV background, fructose supplementation induces fatty liver. 27 Fructose induces the hepatic expression of SCD1 and other lipogenic proteins in SREBP-1c-knockout mice, but not in SCD1-knockout mice, 27 indicating that SCD1 expression is important for the development of fructose-induced fatty liver. However, in ddY mice, sucrose supplementation increased SREBP-1c mRNA and that of its target genes FAS and ACC1 but did not affect SCD1 mRNA expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…On a chow diet, asebia mice with a naturally occurring Scd1 mutation have severe depletion of plasma triglycerides [1,48]. This effect, however, is more modest in mice with a targeted deletion of Scd1 on a SV129 genetic background [19,22,43,48] and absent in mice on a C57BL/6 [42 • ,49 • ] or BTBR [50 • ] background. This may be due to genetic differences between C57BL/6 and SV129 mice, which have previously been shown to influence both hepatic Scd1 expression and development of the metabolic syndrome [51].…”
Section: The Role Of Scd1 In Lipoprotein Metabolismmentioning
confidence: 99%
“…Thus, normal SREBP-1c activation requires adequate levels of MUFA derived from the diet or from endogenous synthesis. Interestingly, these effects are specific to SREBP-1 and do not affect SREBP-2 [22]. We have recently shown that liverspecific deletion of Scd1 using the Cre-loxP system is sufficient to block this carbohydrateinduced lipogenic program [42 •• ].…”
Section: The Effect Of Scd1 Deficiency On Lipid Synthesis and Oxidationmentioning
confidence: 99%
See 2 more Smart Citations